Novel DZ‐SIM Conjugate Targets Cancer Mitochondria and Prolongs Survival in Pancreatic Ductal Adenocarcinoma. Issue 10 (24th July 2022) - Ou, Yan; Wang, Ruoxiang; Chu, Gina Chia‐Yi; Elmadbouh, Omer Hany Miligy; Lim, Adrian; Chung, Leland Wei‐Kuo; Edderkaoui, Mouad; Zhang, Yi; Pandol, Stephen Jacob
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a disease with no effective therapeutics. A novel targeted therapy drug consisting of a tumor‐targeting ligand, near‐infrared (NIR) organic heptamethine carbocyanine dye (DZ), and HMG‐CoA inhibitor simvastatin (SIM), is developed and its efficacy in PDAC is assessed. PDAC cell specific targeting of DZ‐SIM is measured by determining the fluorescence in cells and animals. Mitochondrial bioenergetics and functions are measured by Seahorse and flow cytometry, respectively. Apoptosis is assessed by DNA fragmentation, annexin V/propidium iodide staining, and TUNEL. Markers of cell invasion, epithelial‐to‐mesenchymal transition, and cancer stemness are measured. The effect of DZ‐SIM on survival, tumor growth, and metastasis is measured in the Kras þ/LSLG12D ;Trp53 þ/LSLR172H ;Pdx‐1 −Cre transgenic mice and in syngeneic and subcutaneous PDAC models. NIR fluorescence imaging shows specific localization of DZ‐SIM to cancer, but not to normal cells and tissues. DZ‐SIM significantly inhibits tumor growth and re‐sensitizes therapeutically resistant PDAC cells to conventional therapies. DZ‐SIM kills cancer cells through unique pathways involving decreasing mitochondrial bioenergetics, including oxygen consumption and ATP production, and increasing ROS production. Mitochondrial depletion prevents the effect of DZ‐SIM. Administration of DZ‐SIM in three PDAC animal models results in a marked increase in survival and a decrease in tumor growth and metastasis. Abstract : DZ‐simvastatin (DZ‐SIM), a novel targeted drug consists of a tumor‐targeting near‐infrared organic heptamethine carbocyanine dye and simvastatin. DZ‐SIM is very effective in killing pancreatic cancer cells through targeting mitochondria. DZ‐SIM accumulates in tumors for weeks, but not in healthy organs. DZ‐SIM inhibits cancer cell invasion, sensitizes cancer cells to chemotherapy, and increases the survival of mice with pancreatic cancer.